Can HRM Improve Schools' Performance? - Alex Bryson; Lucy Stokes; David Wilkinson (Institute of Labor Economics (IZA), 2018)
Evidence on schools' performance is confined to comparisons across schools, usually based on value-added measures. We adopt an alternative approach comparing schools to observationally equivalent workplaces in the rest of the British economy using measures of workplace performance that are common across all workplaces. We focus on the role played by management practices in explaining differences in the performance of schools versus other workplaces, and performance across the schools' sector. We find intensive use of HRM practices is correlated with substantial improvement in workplace performance, both among schools and other workplaces. However, the types of practices that improve school performance are different from those that improve performance elsewhere in the economy. Furthermore, in contrast to the linear returns to HRM intensity in most workplaces, improvements in schools' performance are an increasing function of HRM intensity.
Keywords: I21; 330; school performance; human resource management; matching; first differences